A Narrative Review of the Case Reports of Routine Immunization Performance During a Pandemic COVID-19 - Rahayuningsih, Nur; Suwantika, Auliya A.; Diantini, Ajeng; Sinuraya, Rano K. (Universitas Padjadjaran, Indonesia, 2024)
Routine immunization is a program that must ensure adequate coverage as one preventive measure against the transmission of vaccine-preventable disease (VPD). Vaccines are the most cost-effective healthcare investment as it has been shown to prevent and reduce the incidence of disease, disability, and death from VPD, which is estimated to kill 2 – 3 million people each year. As of July 11, 2020, the COVID-19 pandemic has been deemed the worst public health emergency in the world, with over 12 million positive cases and 556,342 fatalities documented in 213 nations. The impact of the pandemic on routine immunization has resulted in higher morbidity and mortality from this VPD in countries with low coverage. This review article comprehensively describes routine immunization services and case reports of immunization performance during the COVID-19 pandemic.